2014
DOI: 10.1021/jf501510d
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Phenolic Compounds in Coffee Melanoidins

Abstract: Phenolic compounds are incorporated into coffee melanoidins during roasting mainly in condensed form (42-62 mmol/100 g) and also in ester-linked form (1.1-1.6 mmol/100 g), with incorporation levels depending on the green coffee chlorogenic acid content. The phenolic compounds are incorporated in different coffee melanoidin populations, but mainly in those soluble in 75% ethanol (82%), a significant correlation between the amount of phenolic compounds and the amount of protein and color characteristics of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 49 publications
(112 reference statements)
9
54
0
2
Order By: Relevance
“…Coffee proteins work as precursors for coffee aroma, flavor, it is because of protein-aroma compound or proteinflavor compound binding. Proteins have a positive correlation with phenolic compounds and coffee mealnoidins, which can be explained by protein and phenolic compound involvement in coffee melanoidin formation (Coelho et al, 2014).…”
Section: Non Volatile Compound Composition Of Coffeementioning
confidence: 98%
See 3 more Smart Citations
“…Coffee proteins work as precursors for coffee aroma, flavor, it is because of protein-aroma compound or proteinflavor compound binding. Proteins have a positive correlation with phenolic compounds and coffee mealnoidins, which can be explained by protein and phenolic compound involvement in coffee melanoidin formation (Coelho et al, 2014).…”
Section: Non Volatile Compound Composition Of Coffeementioning
confidence: 98%
“…Melanoidins are formed in roasting process as Maillard reaction final products (Coelho et al, 2014). There has been reported that polysaccharides, chlorogenic acid and proteins are involved in melanoidin formation (Moreira et al, 2012).…”
Section: Non Volatile Compound Composition Of Coffeementioning
confidence: 99%
See 2 more Smart Citations
“…The β-glucans of ABM are known to stimulate the immune system (Sari, Prange, Lelley, & Hambitzer, 2017;Yamanaka et al, 2012). In recent years, research has been conducted to obtain high-purity and high-activity natural compounds from various types of plants (Coelho et al, 2014;Sheih, Fang, Wu, Chang, & Chen, 2011). In recent years, research has been conducted to obtain high-purity and high-activity natural compounds from various types of plants (Coelho et al, 2014;Sheih, Fang, Wu, Chang, & Chen, 2011).…”
Section: Introductionmentioning
confidence: 99%